Delayed Closure of Open Abdomen in Septic Patients Treated With Negative Pressure Vacuum Therapy and Dynamic Sutures: A 10-Years Follow-Up on Long-Term Complications - Hofmann, Anna Theresa; May, Christopher; Glaser, Karl; Fortelny, René H. (Frontiers in Surgery, 2021)
Introduction Patients with open abdomen after surgical interventions associated with the complication of secondary peritonitis are successfully treated with negative pressure wound therapy. The use of dynamic fascial sutures reduces fascial lateralization and increases successful delayed fascial closure after open abdomen treatment. Methods In 2017 we published the follow-up results of 38 survivors out of 87 open abdomen patients treated with negative pressure wound therapy and dynamic fascial sutures between 2007-2012. In our current study we present the 10-year follow-up results regarding long-term complications with the focus on incisional hernias and pain. Since 2017 seven more patients have died, hence 31 patients were included in the current study. The patients were asked to answer questions about specific long-term complications of OA treatment including pain, the presence of incisional hernias and subsequent surgical interventions. Demographic data and data regarding fascial closure after open abdomen treatment were collected. All results were analyzed quantitatively. The follow-up period was 8-13 years. Results The median age was 69 (30–90) years, and 15 (48.4%) were females. Twenty-four patients (77.4%) responded to the questionnaire: Three patients (12.5%) suffered from pain in the original operating field, all three at rest but not during exercise. None of the patients required analgesic treatment. Eleven patients (45.8%) were found to have incisional hernias. Five out of eleven hernias (45.5%) were treated by surgery and did not declare any pain in the operating field. Among the patients with incisional hernias lower MPI (Mannheimer Peritonitis Index) at the time of primary surgery but more reoperations and treatment days were found. The technique of fascial closure was heterogenic and no differences in the occurrence of incisional hernia could be detected. Conclusion The incidence of incisional hernias after open abdomen treatment is still high, but are associated with little pain in the original operating field. Further studies are required to investigate methods for fascial closure techniques after OA treatment.